Dual hydrophobic modifications toward anion exchange membranes with both high ion conductivity and excellent dimensional stability - Hu, Chuan; Zhang, Qiugen; Wu, Hongyue; Deng, Xiuli; Yang, Qian; Liu, Peng; Hong, Yanzhen; Zhu, Aimei; Liu, Qinglin (Journal of membrane science, 2020)
Anion exchange membrane (AEMs) as a kind of important functional material are widely used in many fields including fuel cell, electrodialysis and water treatment. However, synthetic AEMs generally suffer a pernicious trade-off: high ion-conductive AEMs lack dimensional stability and vice versa. Herein we demonstrate a versatile strategy to prepare the AEMs with both high ion conductivity and excellent dimensional stability (i.e., low swelling ratio) via hydrophobic crosslinking and introducing hydrophobic chains. The hydrophobic length of crosslinkers has great influence on construction of highly efficient ion channels in the AEMs. Amazingly, the hydrophilic poly (phenylene oxide) (PPO) AEM crosslinked by 1,8-diaminooctane has the highest hydroxide conductivity that is further improved to 157.2 mS cm−1 (10% increases) with a low swelling ratio of 12.9% at 80 °C by introducing hydrophobic PPO backbone. This AEM not only overcomes the trade-off between the ion conductivity and the dimensional stability of crosslinked AEMs, but also breaks the upper bound between the ion conductivity and the water uptake. The newly developed strategy of hydrophobic dual-modifications promises to be an effective approach to develop the high-performance AEMs. [Display omitted] •A novel strategy was developed by combining both hydrophobic crosslinker and chain.•The hydrophobic length of crosslinkers has great influence on ion channels of AEMs.•The hydrophobic chains increase ion conductivity and decrease the swelling ratio.•The formed AEM has the OH− conductivity of 157 mS cm−1 with a SR of 12.9% at 80 °C.•This work breaks the trade-off between ion conductivity and dimensional stability.